Impaired endothelial function in patients with cryptogenic stroke and patent foramen ovale is not affected by closure. (25th April 2017) - Lantz, Maria; Kostulas, Konstantinos; Settergren, Magnus; Sjöstrand, Christina
Abstract : Introduction: Patent foramen ovale (PFO) is associated with cryptogenic stroke (CS) and migraine with aura (MA). Endothelial dysfunction (ED) is a risk factor for development of cardiovascular disease, but might also be involved in migraine pathophysiology. Short‐term worsening of migraine has been described after closure of PFO. We evaluated endothelial function in patients with CS and PFO, before and after closure of PFO, and in patients with migraine, whether changes in endothelial function was related to a change in migraine frequency. Material and Methods: Patients with CS and PFO were included; 20 with planned closure of PFO and seven controls on medical treatment only. Endothelial function was assessed by peripheral arterial tonometry (EndoPat R ) and biomarkers of endothelial activation. Patients were followed longitudinally at baseline, day 1, 1 month, and 6 months. A headache diary was used to assess migraine frequency. Result: Mean age of the cohort was 45.4 years, and migraine prevalence was 50% whereof 84.6% had MA. Median EndoPat R index (RHI) at baseline was 1.60 (IQR 1.41‐2.00). There was no change in RHI over time, either in closure patients ( P  = 0.66), nor in controls ( P  = 0.31), and there was no change in biomarkers of endothelial activation. Three migraine patients experienced worsening of migraine frequency directly after closure. Discussion: Endothelial function did not change after closure of PFO. Although patients were lacking cardiovascular risk factors, a high proportion had impaired endothelial function. Whether ED can have predictive value, identifying PFO at higher risk for recurrent stroke warrants further investigations.